Genome-Wide Analysis and Molecular Characterization of Orf Virus Strain UPM/HSN-20 Isolated From Goat in Malaysia - Mangga, Hassana Kyari; Bala, Jamilu Abubakar; Balakrishnan, Krishnan Nair; Bukar, Alhaji Modu; Lawan, Zaharaddeen; Gambo, Auwal; Jesse, Faez Firdaus Abdullah; Noordin, Mustapha M.; Mohd-Azmi, Mohd-Lila (Frontiers in Microbiology, 2022)
Contagious ecthyma commonly known as Orf is a globally important, highly contagious zoonotic, transboundary disease that affects domestic and wild ruminants. The disease is of great economic significance causing an immense impact on animal health, welfare, productivity, and trade. Detailed analysis of the viral genome is crucial to further elucidate the molecular mechanism of ORFV pathogenesis. In the present study, a confluent monolayer of lamb testicle cells was infected with the processed scab sample obtained from an infected goat. The presence of the virus was confirmed using polymerase chain reaction and electron microscopy while its genome was sequenced using next-generation sequencing technology. The genome sequence of Malaysian ORFV strain UPM/HSN-20 was found to contain 132,124bp with a G+C content of 63.7%. The homology analysis indicates that UPM/HSN-20 has a high level of identity 97.3%-99.0% with the other reference ORFV strain. Phylogenetic analysis revealed that ORFV strain UPM/HSN-20 is genetically more closely related to ORFV strain XY and NP from China. The availability of the genome-wide analysis of ORFV UPM/HSN-20 strain from Malaysia will serve as a good platform for further understanding of genetic diversity, ORFV infection, and strategic development for control measures.